Water aerobic training in cardiac rehabilitation programs - A. L. Persiyanova- Dubrova; M. G. Bubnova; I. F. Matveeva; D. M. Aronov (Кардиоваскулярная терапия и профилактика, 2023)
Water aerobic training can be considered as an additional method of exercise in the rehabilitation of cardiovascular patients. The review examines the physiological effects of water training, the potential of its use in different categories of cardiac patients, its advantages, dosing the load and monitoring its intensity in the aquatic environment. The practical aspects of aqua aerobic training are discussed, and research data on its safety and effectiveness in cardiac rehabilitation programs is provided.